2008
DOI: 10.1021/ac800603m
|View full text |Cite
|
Sign up to set email alerts
|

Solution Titration by Wall Deprotonation during Capillary Filling of Silicon Oxide Nanochannels

Abstract: This paper describes a fundamental challenge when using silicon oxide nanochannels for analytical systems, namely the occurrence of a strong proton release or proton uptake from the walls in any transient situation such as channel filling. Experimentally, when fluorescein solutions were introduced into silicon oxide nanochannels through capillary pressure, a distinct bisection of the fluorescence was observed, the zone of the fluid near the entrance fluoresced, while the zone near the meniscus, was dark. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Of particular interest is the intricate interplay among surface chemistry, electrokinetics, and fluid dynamics spanning over molecular and continuum macroscopic length scales [4,5]. It has been demonstrated that the electrokinetic properties at this scale have enabled a range of innovations including those for chemical sensing and bioanalytics [6][7][8][9][10][11][12], energy harvesting systems, [13][14][15][16][17][18], and nanofluidic ion transport [19][20][21][22][23][24][25][26], including enrichment, depletion, and rectification effects [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the intricate interplay among surface chemistry, electrokinetics, and fluid dynamics spanning over molecular and continuum macroscopic length scales [4,5]. It has been demonstrated that the electrokinetic properties at this scale have enabled a range of innovations including those for chemical sensing and bioanalytics [6][7][8][9][10][11][12], energy harvesting systems, [13][14][15][16][17][18], and nanofluidic ion transport [19][20][21][22][23][24][25][26], including enrichment, depletion, and rectification effects [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In experiments performed by (Janssen et al 2008) nanochannels were 40-50 nm deep and 20 lm wide. They used two types of filling solutions: unbuffered KCl solution (mean pH = 7.2) and KCl solution buffered with TRIS (mean pH = 8.5).…”
Section: Resultsmentioning
confidence: 99%
“…The lines were plotted assuming various degrees of surface heterogeneity (kT/c het = 1.0, homogenous surface, solid line; kT/c het = 0.8, dashed line, kT/c het = 0.6, finely dashed line). The data were taken from (Janssen et al 2008) (Sverjensky, 2005) for amorphous silica. This is quite recent, and the most reliable collection of parameters for the 2-pK TLM determined for different oxides and various electrolytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations